ADOPTION OF SUPPLY CHAIN DRIVERS ON SUSTAINABLE PERFORMANCE OF CONSTITUENCY DEVELOPMENT FUNDED PROJECTS IN THE COUNTY GOVERNMENT OF BUNGOMA - Hussein, Wamalwa Moses; Musau, Enock Gideon (International Journal of Supply Chain Management, 2020)
Purpose: The focus of the study was to analyze the influence of supply chain drivers on performance of National Government Constituency Development funded projects in Bungoma County. Methodology: Based on pragmatic worldview the study employed descriptive research design. The target population of the study consisted of five prequalified accredited service providers' contractors in Bungoma County with a total composition of 293 staff from which a sample size of 169 was drawn from the entire population.The data collection tool was the questionnaire which was subjected to pre testing through piloting before actual data collection. The data was analyzed descriptively and inferentially with the aid of SPSS tool and presented by use of tables. Correlation analysis was performed to establish the relationship between variables and multiple regressions to determine the cause effect of the variables. Findings: Result of multiple regressions revealed that supply chain drivers jointly and independently influence performance of NGCDF funded projects in Bungoma County, Kenya. The study findings showed that all study variables (ICT Î²=0.136, p<0.05, material management Î²=0.140, p<0.05, supplier selection Î²=0.317, p<0.05 and contract Î²=0.280, p<0.05 were significant to performance of NGCDF funded projects in Bungoma county. Therefore the study concluded that supply chain practices of ICT, material flow, supplier selection and contractual capacity affects the performance of funded projects. Unique contribution to theory, practice and policy: The study recommends that the county government management in Kenya need to invest in constant training of their employees on effective supply chain practices to enhance their performance and appropriate measures put in place that ensure that potential risks regarding contract management and detected in advance and mitigated to enhance operational performance.